PENGARUH KEBERAGAMAN KARYAWAN TERHADAP KEPUASAN KERJA PADA DINAS PERHUBUNGAN KOTA JAMBI - Said Almaududi; Jonner Simarmata; Zuhri Saputra Hutabarat; Teffu Teffu3 (Information Technology and Science (ITScience), 2023)
Latar belakang: Lorem Ipsum is simply dummy text of the The aim of this research is to know and analyze the impact of employee diversity on job satisfaction in the city relations service.Jambi City Relations Service is a policy in the field of relations in its work territory, technical policy in connection field, administrative implementation includes transportation permits, evaluations and reports related to the field per relationship. Metode penelitian: Dimensions of diversity include religion and tribe while job satisfaction includes the job itself, salary, promotion, supervision, oversight, co-workers and working conditions. Hasil penelitian: The results of SPSS 25 obtained From the Chi-Square Test table asymp sig of 0.776 because of the value of aymp seg 0,776>0,05 it can be concluded that there is no significant relationship between religious diversity and the level of satisfaction it can also be understood that a person's religion diversity has no collateral with the satisfaction of the work obtained. Kesimpulan: Also from the Chi-Square table the test looks asymp sig of 0.316 because the asynp value is 0.318>0,05 then it can be concluded that there is no significant relationship between tribal diversity with the level of satisfaction it can also be understood that a person’s tribal Diversity has no collera with the degree of work achieved.